Butane-based heat pump for advanced GTCC applications: static and dynamic model validation. Issue 1 (1st December 2022) - Anfosso, Chiara; Gini, Lorenzo; Mantelli, Luca; Ferrando, Marco; Reboli, Tommaso; Traverso, Alberto
Abstract: The Thermochemical Power Group (TPG) of the University of Genoa is investigating innovative solutions to increase the flexibility of gas turbine combined cycles (GTCC) and extend their operative range by integrating large size high performance heat pumps. Achieving this goal would make GTCCs more competitive in the future energy market, which will be characterized by a heavy presence of non-dispatchable renewable energy sources. Within this framework, the authors designed and built a new experimental facility to emulate advanced GTCCs at laboratory scale, integrating a 100 kWel micro gas turbine (MGT), a 10 kWel heat pump (HP) and a 180 kWh cold thermal energy storage (TES), with scale-up equations and dynamic models, capable of hardware-in-the-loop tests. The focus of this article is on the HP, which uses n-butane (R600) as working fluid and can be used both to heat and cool down the MGT compressor intake. The HP features one superheater and a 6-cylinder reciprocating compressor, which rotational speed can be continuously varied from 900rpm to 1800rpm. A dynamic model of the HP was developed in TRANSEO, with dedicated Matlab-Simulink® models. This model includes all the components of the HP closed loop, making it possible to simulate its performance and monitor all the main process parameters, such as compressor operation and condensing pressure. This model can be used to simulate the HP in various conditions, including part-load and transient operations, and to aid the design of the advanced GTCC control system. The evaporator and condenser models solve a system of non-linear equations to compute pressure, temperature, and distribution of the different phases of the working fluid along the heat exchangers. Such phase distribution is computed following a moving boundary approach. An experimental campaign was carried out to collect data regarding the stationary performance of the HP. Values of COP and thermal power were analysed as a function of compressor speed and pressure at the condenser, keeping the conditions at the evaporator constant. Then, its transient behaviour was characterized, observing its response to step changes of both evaporator and condenser thermal loads. The model was then successfully calibrated and validated on both stationary and transient data, showing good accuracy. Based on these results, it will be possible to integrate the HP model within larger system simulation tools. Having an accurate digital twin of the whole GTCC integrating HPs and TES will make possible to develop and verify complex control logics on many different scenarios, relying on a safe model-in-the-loop setup, before actual implementation in the field.